A language to express reactivity in the Semantic Web - Tovar, Elsa Liliana; Vidal, María Esther (Rev. Téc. Fac. Ing. Univ. Zulia)
The Semantic Web is a Web to describe by means of metadata the WWW data. In The Semantic Web, knowledge is modeled by using ontology and the reactive behavior is encoded by means of active rules. Hence, active knowledge cannot be used to derive new properties of the data instances, neither new reactive behavior information can be inferred directly from the schema. In this paper, we describe an alternative approach aiming to the enrichment of the Semantic Web with active information. We propose the ontology formalism ACTlON. In ACTION, events are categorized as concepts of the ontology and in conjunction with classes, properties and instances are considered during the query answering and reasoning tasks. We have conducted an empirical experimental study and we have observed that active knowledge representation increases the known information in a third of the active knowledge of the modeled domain. But, the augment of the expressive power implies the augment of the computational complexity and efficient strategies to evaluate reactive query are necessary.